AKTIVITASANTIBAKTERI SAPONIN HASIL ISOLASI ALOE BARBADENSISMILLERTERHADAPSTAPHYLOCOCCUSAUREUS PENYEBAB MASTITIS PADA SAPI PERAH - Imbang Dwi Rahayu (Jurnal Gamma, 2010)
The mastitis in dairy cattle is caused by Staphylococcus aureus. The bacteria are multiresistantto antibiotic. Isolated of Aloe barbadensis Miller, that has antibacterial, saponin is needed to replacesynthetic antibiotic. The research has conducted to tested antibacterial activity of saponin for thegrowth of Staphylococcus aureus.Saponin was exstracted from gel of Aloe vera leafs by n-hexane and methanol. Isolated ofsaponin used to the Coulom Cromatography and Thin Layer Cromatography. It needs H2SO4 foridentifying of saponin. The saponin’s powder was produced by drying process, amylum or dexstrinas kinds of filler. The ratio of saponin and amylum or dexstrin was 80% : 20%. Six levels of saponinwere used in experiment i.e : 1,5%; 3,0%; 6,2%; 12,5%; 25% and 50%. The parameters of theresearch were Minimum Inhibition Concentration (MIC) and cakram disk. The result of experimentwas analysed with descriptively, penicillin was used as positive control.The saponin’s powder give antibacterial activity that higher than saponin’s concentrated. Therewere similarity in antibacterial activity between the saponin’s powder was added amylum withpenicillin.